Primary Mathematics work Book 5A - Lim Li Gek PearIyn; Lim Li Gek PearIyn (Karachi Oxford University Press, 2025)
Practice math skills with Cambridge Primary Mathematics Workbook 5. Covers number systems, geometry, fractions, and more for primary students.